Selected Themes in African Development Studies Economic Growth, Governance and the Environment - Asuelime, Lucky; Yaro, Joseph; Francis, Suzanne; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2014)
Against the background of realities of underdevelopment and economic growth, environmental pressures and global governance challenges, this volume presents a broad picture of contemporary issues in African development. The multi-disciplinary collection presents a variety of important themes, covering land questions, housing, water, health, economic liberalization, climate, environment, and gender. The specific country studies illustrate the diversity of the African continent and demonstrate how unique contexts impact upon different levels of achievement. The volume seeks to present and promote novel analytical frameworks, new conceptual approaches, and empirical accounts of relevance to scholars studying Africa as well as practitioners in African development and policy makers.
Introduction -- Part I: Selected Development Issues in African States -- Part II: Selected Issues in Ghana.
Keywords: Economics; Geography; Development Economics; Environmental economics; Economics/Management Science; Development Economics; Environmental Economics; Political Economy; Economic Geography